2002
DOI: 10.1159/000065028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hemodialysis Membrane and Permeability on Neutrophil Transmigration in vitro

Abstract: Background/Aim: The impact of dialysis membrane permeability on neutrophil transmigration properties in vitro was examined in the present study. This issue has not been fully scrutinized before. Methods: We studied the capacity of neutrophils collected from a group of dialysis patients randomly treated with cuprophan, low- or high-flux polysulfone, to transmigrate in vitro through a membrane covered with fibronectin (a main constituent of the endothelial basement membrane). The hemodialysis-induced quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
4
5
0
Order By: Relevance
“…The CD11b expression of neutrophils from newborns was not affected by the delivery stress and was lower compared with adults, as previously reported (26). The increased transmigration ability was not associated with a concomitant increase in CD11b expression, a finding in line with results from human adults (27).…”
Section: Discussionsupporting
confidence: 89%
“…The CD11b expression of neutrophils from newborns was not affected by the delivery stress and was lower compared with adults, as previously reported (26). The increased transmigration ability was not associated with a concomitant increase in CD11b expression, a finding in line with results from human adults (27).…”
Section: Discussionsupporting
confidence: 89%
“…In vitro activation with fMLP induced a significant increase in the expression of CD11b on monocytes and neutrophils in the peripheral circulation and at the sites of interstitial inflammation, both in patients on highflux hemodialysis/hemodiafiltration and healthy subjects. The preserved capacity of both monocytes and neutrophils to express CD11b at the sites of interstitial inflammation in patients on high-flux hemodialysis/hemodiafiltration, as shown by our findings, may have important biological consequences in terms of an adequate performance of leukocyte functions in which the CD11b molecule plays a key role (Thylen et al 1997;Moshfegh et al 2002). Extravasated neutrophils and monocytes from patients on high-flux hemodialysis/hemodiafiltration showed a maintained response to fMLP as a second inflammatory stimulus after extravasation.…”
Section: Cd11bsupporting
confidence: 62%
“…The dialysis membrane permeability and flux are also of importance in determining the acute and chronic effects of hemodialysis on the inflammatory system. High-flux polysulfone dialysis, as opposed to low-flux polysulfone and cuprophane treatment, has been shown to improve the transmigration of circulating neutrophils (Moshfegh et al 2002). High-flux dialysis membranes decrease the levels of the two degranulation inhibitory proteins (angiogenin and complement factor D), which could contribute to the maintained respiratory burst and phagocytic capacity seen in patients on high-flux hemodialysis (Horl 2002).…”
Section: Patients On Hemodialysismentioning
confidence: 99%
“…The in vivo data in the present study are in line with our previously reported data on the impact of dialysis membrane permeability on neutrophil transmigration properties in vitro. In that study, we demonstrated that high-flux polysulfone dialysis, as opposed to low-flux polysulfone and cuprophan treatment, improves the transmigration properties of peripheral neutrophils [26] .…”
Section: Discussionmentioning
confidence: 77%